2022
DOI: 10.3390/life12071072
|View full text |Cite
|
Sign up to set email alerts
|

ANCA-Associated Vasculitis May Result as a Complication to Both SARS-CoV-2 Infection and Vaccination

Abstract: In the last two years, our world experienced one of the most devastating and fast-exploding pandemic, due to the wide spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The scientific community managed to develop effective vaccines, the main weapons to shield the immune system and protect people. Nevertheless, both SARS-CoV-2 infection and the vaccination against it have been associated with the stimulation of inflammatory cells such as T and B lymphocytes that results in a cytokine storm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…AAV is classified into three types based on clinical features, namely granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic GPA (EGPA) [ 111 ]. A total of 17 new-onset AAV cases have been reported, including 5 cases of PR3-ANCA vasculitis, 9 cases of MPO-ANCA vasculitis, and 3 cases of dual-positive MPO- and PR3-ANCA vasculitis [ [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] ]. The majority of cases were women (11/17, 64.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AAV is classified into three types based on clinical features, namely granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic GPA (EGPA) [ 111 ]. A total of 17 new-onset AAV cases have been reported, including 5 cases of PR3-ANCA vasculitis, 9 cases of MPO-ANCA vasculitis, and 3 cases of dual-positive MPO- and PR3-ANCA vasculitis [ [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] ]. The majority of cases were women (11/17, 64.7%).…”
Section: Resultsmentioning
confidence: 99%
“…All patients received steroid therapy, while some also received hemodialysis (2/17,11.8%), plasmapheresis (7/17,41.2%), cyclophosphamide (11/17,64.7%), and rituximab(6/17,35.3%). Christodoulou et al reported the first case of a healthy patient who developed de novo MPO-ANCA vasculitis shortly after COVID-19 vaccination and responded to steroids and cyclophosphamide but relapsed immediately after COVID-19 infection [ 121 ]. This finding suggests that both SARS-CoV-2 infection and vaccination may induce vasculitis and involve similar immune mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Anderegg MA, 2021 [32] 81/Male mRNA-1273 2nd dose ND PR3-ANCA pauci-immune crescentic GN with capillary necrosis and vasculitis present in the renal vessel walls Dube GK, 2021 [33] 29/Female BNT162b2mRNA 2nd dose 16 d MPO-ANCA pauci-immune crescentic GN Feghali EJ, 2021 [34] 58/Male mRNA-1273 2nd dose 4 d anti-PR3-associated ANCA GN Hakroush S, 2021 [35] 79/Female BNT162b2mRNA 2nd dose 2 wk MPO-ANCA associated vasculitis presenting with pauci-immune crescentic GN Ritter A, 2021 [36] 69/Male BNT162b2mRNA 2nd dose 33 d MPO-ANCA AAV with massive rhabdomyolysis and pauci-immune crescentic GN Sekar A, 2021 [37] 52/Male mRNA-1273 2nd dose 2 wk PR3-ANCA pauci-immune necrotizing and crescentic GN Shakoor MT, 2021 [38] 78/Female BNT162b2mRNA 2nd dose 2 wk Renal-limited MPO-AAV Villa M, 2021 [39] 63/Male ChAdOx1 nCoV-19 1st dose 1 wk P-ANCA-associated pauci-immune GN Al-Yafeai Z, 2022 [40] 62/Female BNT162b2mRNA 1st dose 4 wk PR3-ANCA-associated vasculitis Cano-Gámez T, 2022 [41] 51/Female ChAdOx1 nCoV-19 3rd dose ND MPO-ANCA-associated rapidly progressive GN Christodoulou M, 2022 [42] 72/Female mRNA-1273 2nd dose 2 wk MPO-ANCA pulmonary-renal syndrome (alveolar hemorrhage and rapidly progressive GN) Prabhahar A, 2022 [43] 51/Male ChAdOx1 nCoV-19 1st dose 15 d PR-3 AAV with pauci-immune crescentic GN So D, 2022 [44] 42/Male BNT162b2mRNA 2nd dose ND MPA with elevated MPO-antibodies and pauci-immune GN Suzuki M, 2022 [45] 72/Male BNT162b2mRNA 2nd dose 1 d MPO-AAV with severe pauci-immune crescentic GN Kawamura T, 2023 [46] 71/Female BNT162b2mRNA 2nd dose 1 wk MPO-AAV with manifestations of renal involvement, general symptoms, and the definite presence of MPO-ANCA, as an underlying disease of rapidly progressive GN AAV = antineutrophil cytoplasmic antibodies-associated vasculitis, AKI = acute kidney injury, ANCA = antineutrophil cytoplasmic antibodies, GN = glomerulonephritis, MPA = microscopic polyangiitis, MPO = myeloperoxidase, PR3 = proteinase 3, RLV = renal limited vasculitis.…”
Section: Onset Of Symptoms Aav Diagnosismentioning
confidence: 99%
“…Interestingly, isolated case reports described the occurrence of renal TMA in AAV patients, an association that may pose diagnostic and therapeutic challenges. [25–31] In addition, some cases of both de novo and relapses of AAV and/or TMAs after anti-SARS-CoV2 vaccination have been reported [32–53]…”
Section: Introductionmentioning
confidence: 99%
“…It remains controversial whether SARS-CoV-2 infection or vaccination may have had an impact on epidemiology of systemic vasculitis. Several case reports of de novo vasculitis, affecting medium, or small vessels, following either infection or vaccination against COVID-19, during the pandemic outbreak (11). One retrospective study conducted in Australia compared the frequency of new cases of GCA during the period April 2020-August 2021 to the pre-pandemic period, finding a reduction in the incidence of GCA of 55%.…”
Section: Systemic Vasculitis Following Either Infection or Vaccinatio...mentioning
confidence: 99%